I'm trying to prove the following statements in Folland's book.

Let $(X,\mathcal{M},\mu)$ be a measure space. If $f_n\to f$ in measure and $g_n\to g$ in measure, then $f_n+g_n\to f+g$ in measure and $f_ng_n\to fg$ in measure (in this last case, assume $\mu(X)<\infty$).

The first one is already done, but the second one is giving me trouble.

My attempt: We can take subsequences $f_{n_k}$ and $g_{n_k}$ such that $f_{n_k}\to f$ a.e. and $g_{n_k}\to g$ a.e. In this case, we know that $f_{n_k}g_{n_k}\to fg$ a.e. Note that $\mu(X)<\infty$, so we can use Egoroff's theorem to conclude that $f_{n_k}g_{n_k}\to fg$ almost uniformly. Finally, almost uniform convergence implies convergence in measure, therefore $f_{n_k}g_{n_k}\to fg$ in measure.

The problem is that I just have convergence in measure for some subsequence of $f_ng_n$ and I need convergence in measure for the whole sequence. Also I don't know if using Egoroff's theorem is unnecessary, if this is the case, I would appreciate to see some more elementary prove.

Detail: We say that $f_n\to f$ almost uniformly if for every $\varepsilon > 0$ there is some $E\subset X$ measurable, such that $\mu(E) <\varepsilon$ and $f_n\to f$ uniformly on $E^c$.

Thank you!


3 Answers 3


There is something which is sometimes called the subsequence principle. It states that $x_n \to x$ holds if and only if every subsequence $(x_{n_k})_k$ admits a further subsequence $(x_{n_{k_l}})_l$, which converges to $x$. Note that the limit $x$ has to be fixed.

This holds as soon as the notion of convergence is induced by a topology.

This should help you here.

Interesting sidenote: Using this property, one can show that convergence a.e. (of measurable functions on $\Bbb{R}$) is not induced by a topology.

For the proof of the principle, note that "$\Rightarrow$" is trivial (use $(x_{n_k})_k$ itself for the "further subsequence". For "$\Leftarrow$", assume that $x_n \to x$ is false. Then (by definition) there is a neighborhood $U$ of $x$ such that for each $N\in \Bbb{N}$, there is some $n_N \geq N$ with $x_{n_N}\notin U$. Inductively, this allows to construct a subsequence $(x_{n_k})_k$ with $x_{n_k}\notin U$ for all $k$. But by assumption, there is a further subsequence $(x_{n_{k_l}})_l$ which converges to $x$. In particular, for $l$ large enough, $x_{n_{k_l}}\in U$ (because $U$ is an neighborhood of $x$), contradiction.

EDIT: Here is another possible proof: Using the subsequence principle, you can also show the following equivalence on a space of finite measure:

A sequence $(f_n)_n$ of measurable functions converges in measure to $f$ iff every subsequence $(f_{n_k})_k$ has a further subsequence $(f_{n_{k_\ell}})_\ell$ which converges pointwise a.e. to $f$.

Once you have shown this characterization, you can derive your claim as a corollary.

  • $\begingroup$ Do you have a link with the proof of this principle. I don't want to use results without knowing their proofs. $\endgroup$
    – Integral
    Jan 25, 2015 at 16:25
  • $\begingroup$ Don't worry about that anymore, I could help myself. $\endgroup$
    – Integral
    Jan 25, 2015 at 17:03
  • 1
    $\begingroup$ We now there is a subsequence of $\{f_2, f_4, \ldots\}$ converging a.e. to $f$, suppose this subsequence is $\{f_{10}, f_{20},\ldots\}$, with the index being all multiples of $10$. On the other side, we know there is a subsequence of $\{g_2, g_4,\ldots\}$ converging a.e. to $g$, suppose this subsequence is $\{g_{12}, g_{22},\ldots\}$, with the index being all multiples of $10$ plus $2$. In this view, there is no way in can use the product os this subsequences to argue something, because we need products of the form $f_ng_n$, the indexes must agree. $\endgroup$
    – Integral
    Jan 26, 2015 at 14:11
  • 2
    $\begingroup$ In your example, consider the sequence $(h_n)_n = \{g_10, g_20, \dots\}$. This sequence still converges in measure to $g$, since it is a subsequence of $(g_n)_n$. Hence, there is a subsequence of $(h_n)_n$, which maybe takes each 3rd entry of $(h_n)_n$ such that $(h_{3n})_n$ converges pointwise a.e. to $g$. But $(h_{3n})_n = (g_{30}, g_{90}, \dots)$. Since $(f_{30}, f_{90}, \dots)$ is also a subsequence of $(f_{10}, f_{20}, \dots)$, which we know converges pointwise a.e., everything is fine. $\endgroup$
    – PhoemueX
    Jan 26, 2015 at 14:20
  • 1
    $\begingroup$ Now it's 100% done. Thank you very much your patience. I really learned a lot. $\endgroup$
    – Integral
    Jan 26, 2015 at 22:49

I prove PhoemueX's claim as follows.

Let $(X,\mathcal{F},\mu)$ be a measure space with $\mu(X)<\infty$. Let $f_{n}:X\rightarrow\mathbb{R}$ and $f:X\rightarrow\mathbb{R}$ be measurable functions. Then the following are equivalent:

(1) $f_{n}\rightarrow f$ in measure,

(2) Every subsequence of $\{f_{n}\}$ has a subsequence that converges to $f$ a.e.

Proof: To prove $(1)\Rightarrow(2)$: Let $\{f_{n_{k}}\}$ be a subsequence of $\{f_{n}\}$. To simplify notation, we denote $g_{k}=f_{n_{k}}$. Clearly $g_{n}\rightarrow f$ in measure. Choose integers $n_{k}$ inductively such that $n_{1}<n_{2}<\ldots$ and $\mu\left(\left[|g_{n_{k}}-f|\geq\frac{1}{k}\right]\right)\leq\frac{1}{2^{k}}$. To further simplify notation, let $h_{k}=g_{n_{k}}$. We assert that $h_{n}\rightarrow f$ a.e.. Define $A=\{x\in X\mid\lim_{n}h_{n}(x)=f(x)\}$. Observe that $$ A^{c}=\bigcup_{l=1}^{\infty}\bigcap_{N=1}^{\infty}\bigcup_{n=N}^{\infty}\{x\mid|h_{n}(x)-f(x)|\geq\frac{1}{l}\}. $$ We go to show that, for each $l\in\mathbb{N}$, $\mu\left(\bigcap_{N=1}^{\infty}\bigcup_{n=N}^{\infty}\{x\mid|h_{n}(x)-f(x)|\geq\frac{1}{l}\}\right)=0$. For each $N$, denote $B_{N}=\bigcup_{n=N}^{\infty}\{x\mid|h_{n}(x)-f(x)|\geq\frac{1}{l}\}$. For $n\geq l$, we have $\{x\mid|h_{n}(x)-f(x)|\geq\frac{1}{l}\}\subseteq\{x\mid|h_{n}(x)-f(x)\mid\geq\frac{1}{n}\}$, so for any $N\geq l$, $$ \mu\left(B_{N}\right)\leq\sum_{n=N}^{\infty}\mu\left(\{x\mid|h_{n}(x)-f(x)|\geq\frac{1}{l}\}\right)\leq\sum_{n=N}^{\infty}\mu\left(\{x\mid|h_{n}(x)-f(x)|\geq\frac{1}{n}\}\right)\leq\sum_{n=N}^{\infty}\frac{1}{2^{n}}. $$ Observe that $B_{1}\supseteq B_{2}\supseteq\ldots$ and $\mu$ is finite, we have $\mu(\cap_{N}B_{N})=\lim_{N\rightarrow\infty}\mu(B_{N})=0$. Therefore, $\mu(A^{c})=0$ and hence $h_{n}\rightarrow f$ a.e.

To prove $(2)\Rightarrow(1)$: Prove by contradiction. Suppose the contrary that $f_{n}\not\rightarrow f$ in measure. Then there exists $\delta_{1}>0$ such that $\mu\left(\left[|f_{n}-f|\geq\delta_{1}\right]\right)\not\rightarrow0$. There further exist $\delta_{2}>0$ and a subsequence $(n_{k})$ such that for each $k$, $\mu\left(\left[|f_{n_{k}}-f|\geq\delta_{1}\right]\right)\geq\delta_{2}.$ Define $\delta=\min(\delta_{1},\delta_{2})$. In particular, we have $\mu\left(\left[|f_{n_{k}}-f|\geq\delta\right]\right)\geq\delta$. To further simplify notation, denote $g_{k}=f_{n_{k}}$. Then $(g_{n})$ is a subsequence of $(f_{n})$ and $\mu\left(\left[|g_{n}-f|\geq\delta\right]\right)\geq\delta$ for each $n$. By assumption, $(g_{n})$ has a subsequence $(g_{n_{k}})$ that converges to $f$ a.e.. Define $D=\{x\mid g_{n_{k}}(x)\rightarrow f(x)\}$, then $$ D^{c}=\bigcup_{l=1}^{\infty}\bigcap_{N=1}^{\infty}\bigcup_{k=N}^{\infty}\{x\mid|g_{n_{k}}(x)-f(x)|\geq\frac{1}{l}\}. $$ Choose $l$ such that $\frac{1}{l}<\delta$. Note that $\mu(D^{c})=0$, and in particular, $\mu\left(\bigcap_{N=1}^{\infty}\bigcup_{k=N}^{\infty}\{x\mid|g_{n_{k}}(x)-f(x)|\geq\frac{1}{l}\}\right)=0.$ Note that $\mu$ is finite and $\left(\bigcup_{k=N}^{\infty}\{x\mid|g_{n_{k}}(x)-f(x)|\geq\frac{1}{l}\}\right)_{N}$ is a decreasing sequence of measurable sets. Therefore $$ \lim_{N\rightarrow\infty}\mu\left(\bigcup_{k=N}^{\infty}\{x\mid|g_{n_{k}}(x)-f(x)|\geq\frac{1}{l}\}\right)=\mu\left(\bigcap_{N=1}^{\infty}\bigcup_{k=N}^{\infty}\{x\mid|g_{n_{k}}(x)-f(x)|\geq\frac{1}{l}\}\right)=0. $$ Choose $N$ such that $\mu\left(\bigcup_{k=N}^{\infty}\{x\mid|g_{n_{k}}(x)-f(x)|\geq\frac{1}{l}\}\right)<\delta$. Observe that for each $k\geq N$, $\{x\mid|g_{n_{k}}(x)-f(x)|\geq\frac{1}{l}\}\supseteq\{x\mid|g_{n_{k}}(x)-f(x)|\geq\delta\}$, so $$ \mu\left(\bigcup_{k=N}^{\infty}\{x\mid|g_{n_{k}}(x)-f(x)|\geq\frac{1}{l}\}\right)\geq\mu\left(\{x\mid|g_{n_{N}}(x)-f(x)|\geq\delta\}\right)\geq\delta $$ which is a contradiction.


By using the claim, we can prove that $f_{n}\rightarrow f$ and $g_{n}\rightarrow g$ in measure $\Rightarrow$ $f_{n}g_{n}\rightarrow fg$ in measure immediately.

For, let $\left(f_{n_{k}}g_{n_{k}}\right)_{k}$ be an arbitrary subsequence of $(f_{n}g_{n})_{n}$. $f_{n}\rightarrow f$ in measure implies that for the subsequence $(f_{n_{k}})_{k}$, there exists a subsequence $(f_{n_{k_{l}}})_{l}$ such that $f_{n_{k_{l}}}\rightarrow f$ a.e.. $g_{n}\rightarrow g$ in measure implies that for the subsequence $(g_{n_{k_{l}}})_{l}$, there exists a further subsequence $(g_{n_{k_{l_{p}}}})_{p}$ such that $g_{n_{k_{l_{p}}}}\rightarrow g$ a.e.. Now, we have $f_{n_{k_{l_{p}}}}g_{n_{k_{l_{p}}}}\rightarrow fg$ a.e.. By the claim, we have $f_{n}g_{n}\rightarrow fg$ in measure.


An alternative method is based on the result here product case

And the rest of proof is based on the first result


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.